Near Miss Cases in Women of Bangladesh (Community Based Medical Journal, 2013)
A Near Miss Case denotes a woman experiencing at least one near miss case event. The Near miss case events include hemorrhage, hypertensive disorder during pregnancy, dystocia, infection and anemia. The present study focuses about near miss case events in three women with different manifestations - 1st woman had hypertensive disorder in pregnancy, 2nd woman had dystocia, hemorrhage and infection disorder and 3rd woman had infection and hemorrhage. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14187 Community Based Medical Journal Vol.2(1) 2013 63-65